Environmental and sensitization variations among asthma and/or rhinitis patients between 2008 and 2018 in China. Issue 2 (2nd February 2022) - Wang, Wanjun; Wang, Jianhong; Song, Guihua; Xie, Hua; Lin, Xiaoping; Chai, Ruonan; Zhu, Rongfei; He, Yong; Tang, Jun; Wang, Junge; Yang, Jinghua; Zhi, Lili; et al.
Abstract: Background: Little is known about the changes in allergen sensitization in China secondary to the environmental variations over the past decade. We aimed at investigating the variations in sensitization among asthma and/or rhinitis patients in China between 2008 and 2018. Methods: This study analyzed cross‐sectional data from national surveys conducted in China in 2008 and 2018. After finishing the questionnaire, participants underwent serum specific IgE measurements. A total of 2322 and 2798 patients were enrolled in 2008 and 2018, respectively. The significance of differences in sensitization rates among four regions of China were assessed. Correlation analysis was used to identify the associations of sensitization with climate change and planting of Artemisia desertorum between the two surveys. Results: Compared with 2008, the general sensitization rate to mites significantly increased in 2018, which ranked highest among all tested allergens. Sensitization to pollens, especially Artemisia vulgaris, showed the greatest increase in the north. The annual mean temperature, rainfall and relative humidity in all four regions, and the Artemisia desertorum coverage in the northeastern area, increased significantly in 2018 as compared with 2008. From 2008 to 2018, an increase in Dermatophagoides pteronyssinus sensitization was significantly associated with an increase in relative humidity ( r  = 0.54, p  = 0.037). The increase in A. vulgaris sensitization was significantly associated with the increase in the A. desertorum planting area ( r  = 0.67, p  = 0.006) and with a decrease in rainfall ( r  = −0.59, p  = 0.021). Conclusions: House dust mites remain the most important allergen in Chinese individuals with asthma and/or rhinitis. Pollen sensitization dramatically increased in northern China. Increases in sensitization to dust mites and Artemisia were related to the increases in humidity and planting area of A. desertorum .